ABOUT NOTION OF MEASUREMENT RELIABILITY WHEN MONITORING OPERATION MODES OF POWER UNITS - V. A. Anishchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Monitoring process of measurement reliability in respect of variables that characterize operation modes of power units is investigated in the paper. Control algorithms based on the minimax criterion have been developed. These algorithms take into account the uncertainty in the notion of measurement reliability, the probability distribution laws for the variables under control, and the values of monitoring errors.